Vasculature-Associated Lymphoid Tissue: A Unique Tertiary Lymphoid Tissue Correlates With Renal Lesions in Lupus Nephritis Mouse Model - Masum, Md. Abdul; Ichii, Osamu; Elewa, Yaser Hosny Ali; Otani, Yuki; Namba, Takashi; Kon, Yasuhiro (Frontiers in Immunology, 2020)
Lupus nephritis (LN) is a common complication in young patients and the most predominant cause of glomerulonephritis. Infiltrating immune cells and presence of immunocomplexes in the kidney are hallmarks of LN, which is closely associated with renal lesions (RLs). However, their regulatory mechanism in the kidney remains unclear, which is valuable for prevention of RL development. Here, we show the development of vasculature-associated lymphoid tissue (VALT) in LN, which is related to renal inflammatory cytokines, indicating that VALT is a unique tertiary lymphoid tissue. Transcriptomic analysis revealed different chemokines and costimulatory molecules for VALT induction and organization. Vascular and perivascular structures showed lymphoid tissue organization through lymphorganogenic chemokine production. Transcriptional profile and intracellular interaction also demonstrated antigen presentation, lymphocyte activity, clonal expansion, follicular, and germinal center activity in VALT. Importantly, VALT size was correlated with infiltrating immune cells in kidney and RLs, indicating its direct correlation with the development of RLs. In addition, dexamethasone administration reduced VALT size. Therefore, inhibition of VALT formation would be a novel therapeutic strategy against LN.